QUALITY OF MILK FATTY ACID DURING LATE LACTATION IN DAIRY GOAT FED ON PUFA-DIET SUPPLEMENTED WITH YEAST AND - Sulistyowati, E.; Sudarman, A.; Wiryawan, K.G.; Toharmat, T. (Diponegoro University, 2013)
Yeast and curcumin of C. xanthorrhiza Roxb could be added into concentrate containingpolyunsaturated fatty acid (PUFA) to improve milk fatty acid quality of dairy goat. There were fivetreatments (PD0: PUFA- diet with no additive; PDA: PUFA- diet with 3 Asifit tablets; PDY: PUFA- dietwith 5 g yeast; PDC: PUFA- diet with 20 g curcuma powder; and PDM: PUFA- diet with a mixture of 5g yeast and 20 g curcuma powder) applied onto 20 dairy goats during late lactation (4.6 ± 0.55 monthsof lactation). The treatments were allocated according to a completely completely randomized blockdesign. Results demonstrated that diet containing PUFA supplemented with 5 g yeast and 20 g curcumawere high in total fatty acid, medium chain fatty acid (MCFA), and long chain fatty acid (LCFA). Milkof goats with this treatment showed high in mono unsaturated fatty acid (MUFA) and MUFA; while itwas low in short chain fatty acid (SCFA), n6/n3 ratio, and atherogenicity index. These qualities wereoptimally considered good in terms of healthier product. Therefore, the PUFA- diet with 5 g yeast and20 g curcuma was a reasonable choice to be applied for dairy goat.